The Design on Quality System Model of FTIK IAIN Pontianak in SNPT 2015 and QMS ISO 9001:2015 - Muhtifah, Lailial; Muskania, Ricka Tesi (Jurnal Pendidikan Islam, 2018)
The Faculty of Teacher Training integrated SNPT (National Standard for Higher Education) 2015 and QMS (Management Quality Standard) ISO 9001: 2015 in Quality Model Design FTIK (Faculty of Teacher Training and Education). This paper is aimed to analyze and to create a model for quality improvement of FTIK IAIN Pontianak. This a research-and-development study (R&D) with a mixed method. The stages include the introduction, model design development, and expert’s model validation in quality testing at the Islamic Education major (PAI) and Arabic Education (PBA), and Islamic Elementary School Teacher Training (PGMI). This paper shows that there are four majors in FTIK that are still below the standard of SNPT 2015. FTIK innovated to find Model ISQEE to improve the quality of the four majors at FTIK IAIN Pontianak with SNPT 2015 and QMS ISO 9001: 2015.